1993
DOI: 10.1002/yea.320091005
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the amino acid permeases in nitrogen‐limited continuous cultures of the yeast Saccharomyces cerevisiae

Abstract: In the yeast Saccharomyces cerevisiae, there is a general amino acid permease, regulated by nitrogen catabolite repression, and several specific permeases whose nitrogen regulation is not well understood. In this study, we used continuous cultures to analyse the effect of nitrogen limitation and pH on the activity of general and several specific amino acid permeases. General permease activity was maximal in severe nitrogen limitation and diminished 400-fold in cells grown under nitrogen excess. For the specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…From the screening, we also identified the histidine and methionine transporters Hip1 and Mup1. Unlike NCR-sensitive permeases that transport amino acids primarily for use as a source of nitrogen, Hip1 and Mup1 are though to transport specific amino acids for direct use in protein synthesis when the nitrogen conditions are favorable (39). HIP1 and MUP1 expression is induced by the SPS amino acid-sensing system and has been shown to be down-regulated in the presence of a poor nitrogen source, and this down-regulation requires the presence of Gap1 at the plasma membrane (5).…”
Section: Fig 4 Loss Of Bul1 and Bul2 Function Results In Vacuolar Dmentioning
confidence: 99%
“…From the screening, we also identified the histidine and methionine transporters Hip1 and Mup1. Unlike NCR-sensitive permeases that transport amino acids primarily for use as a source of nitrogen, Hip1 and Mup1 are though to transport specific amino acids for direct use in protein synthesis when the nitrogen conditions are favorable (39). HIP1 and MUP1 expression is induced by the SPS amino acid-sensing system and has been shown to be down-regulated in the presence of a poor nitrogen source, and this down-regulation requires the presence of Gap1 at the plasma membrane (5).…”
Section: Fig 4 Loss Of Bul1 and Bul2 Function Results In Vacuolar Dmentioning
confidence: 99%
“…The proton excess generated during amino acid synthesis must be pumped out of the cell to keep the internal pH constant, resulting in the strong acidification of the medium, which affects ammonium uptake and growth (WIAME et al 1985). It has been reported that the affinity of permeases for amino acids changes with the charge on the amino acid (OLIVEIRA et al 1993). It has been reported that the affinity of permeases for amino acids changes with the charge on the amino acid (OLIVEIRA et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…2). As the PMF is known to be involved in fungal amino acid transport (Kropf et al, 1984;Eddy & Hopkins, 1988;Olivera et al, 1993;Pokorný et al, 2004), the effect of uncoupler was tested. The degree of inhibition increased from about 10-30 % in dormant conidia to 80-90 % in germinated conidia, suggesting an increased requirement of PMF by amino acid permeases during germination.…”
Section: Discussionmentioning
confidence: 99%